Community Participation In The Exclusive Breastfeeding Program In Temanggung - C. Ermayani Putriyanti (CV. AFDIFAL MAJU BERKAH, 2025)
Exclusive breastfeeding not only increases immunity, reduces infant and toddler mortality rates due to diarrhea and respiratory tract infections. There is a relationship between exclusive breastfeeding and high levels of child intelligence, increased income when aged 30 years, and prevents cancer later in life. The impact of breastfeeding reduces postpartum bleeding, prevents breast cancer and ovarian cancer. This study aims to determine community participation in the exclusive breastfeeding program in the Parakan Health Center work area. Data were obtained by conducting in-depth interviews, observation and documentation. Community participation in supporting exclusive breastfeeding has not been maximized, there has been no development of new strategies related to the exclusive breastfeeding program, the community has not been involved in program planning, there has been no special allocation of funds for exclusive breastfeeding program activities. The cause of breastfeeding failure is highest in working mothers and families, especially grandmothers. Community participation needs to be increased through cooperation with community leaders, religious leaders, youth organizations in the socialization of exclusive breastfeeding. There needs to be a policy for allocating village funds for the socialization of exclusive breastfeeding, the knowledge of cadres regarding exclusive breastfeeding is increased, so that cadres can provide counseling and not just remind. There needs to be cooperation with companies or factories regarding the policy of providing rooms for expressing and breastfeeding babies.